2007
DOI: 10.1007/s00330-007-0639-5
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial tagging with steady state free precession techniques and semi-automatic postprocessing—impact on diagnostic value

Abstract: Our aim was to determine the diagnostic value of myocardial tagging sequences with regard to the evaluable share of the cardiac cycle. Thirty-three patients were examined at 1.5 T using tagging sequences with gradient-echo (GRE) readout, 18 patients at 1.5 T with steady-state free precession (SSFP), and 11 patients at 3 T using GRE. Two observers graded image quality and determined the share of the cardiac cycle for which postprocessing could be performed (1, optimal; 2, little interaction; 3, whole cycle asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…When compared to SPGR with ramped flip angles, the ramped flip angle bSSFP sequence provided double the tagging contrast during the same scan time [88]. In 2007, Johnson et al conducted a study to assess the diagnostic value of myocardial tagging with bSSFP, and concluded that bSSFP was superior to the gradient echo sequence [89]. The improved tagging contrast and tag persistence with bSSFP facilitated post-processing and enabled diastolic function analysis.…”
Section: Data Acquisition Strategiesmentioning
confidence: 99%
“…When compared to SPGR with ramped flip angles, the ramped flip angle bSSFP sequence provided double the tagging contrast during the same scan time [88]. In 2007, Johnson et al conducted a study to assess the diagnostic value of myocardial tagging with bSSFP, and concluded that bSSFP was superior to the gradient echo sequence [89]. The improved tagging contrast and tag persistence with bSSFP facilitated post-processing and enabled diastolic function analysis.…”
Section: Data Acquisition Strategiesmentioning
confidence: 99%
“…However, imaging at high fields may also introduce additional SSFP off‐resonance and flow artifacts due to increased susceptibility effects. Although standard tagging based on RF‐spoiled gradient echo imaging has been evaluated at 1.5 and 3T (19, 20), no results on SSFP‐tagging at 3T and no direct comparison of SSFP‐tagging at different field strengths have been reported to date.…”
mentioning
confidence: 99%